2017
DOI: 10.1590/1678-98652017000100009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a mobile application for estimation of food intake

Abstract: A B S T R A C T ObjectiveEvaluate the use of the Nutrabem (São Paulo, Brasil) mobile application as a tool for measurement of food intake among university students. MethodsCross-sectional study of a random sample of 40 undergraduate students at the Universidade Federal de São Paulo, Campus Baixada Santista. Food intake data were estimated using the Nutrabem app and the 24-hour dietary recall. Intakes of energy, carbohydrates, proteins, lipids, calcium, iron, and vitamin C were calculated. The intake of food gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The period of app use ranged mostly from 2 to 7 d and contained at least 1 weekend day for most studies, while 2 studies asked participants to record every day for 3 mo ( 28 , 29 ). The app use was on nonconsecutive days for 3 of the studies ( 12 , 30 , 36 ). Ten studies used 24HRs as the only reference method for 2 d ( n = 6) ( 16 , 20 , 28 , 34 , 37 , 38 ) or 3 d ( n = 4) ( 32 , 33 , 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The period of app use ranged mostly from 2 to 7 d and contained at least 1 weekend day for most studies, while 2 studies asked participants to record every day for 3 mo ( 28 , 29 ). The app use was on nonconsecutive days for 3 of the studies ( 12 , 30 , 36 ). Ten studies used 24HRs as the only reference method for 2 d ( n = 6) ( 16 , 20 , 28 , 34 , 37 , 38 ) or 3 d ( n = 4) ( 32 , 33 , 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The app use was on nonconsecutive days for 3 of the studies ( 12 , 30 , 36 ). Ten studies used 24HRs as the only reference method for 2 d ( n = 6) ( 16 , 20 , 28 , 34 , 37 , 38 ) or 3 d ( n = 4) ( 32 , 33 , 35 , 36 ). One study used an FFQ ( 29 ), 1 study used dietary records ( 30 ), 2 studies used an accelerometer (to measure energy expenditure) ( 12 , 31 ), and 1 study used a combination of accelerometer, 24HRs, and dietary records ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ali et al (143), participants were able to choose from predetermined portion sizes if they indicated that they consumed foods from certain restaurants that were included in the app. In some studies, providing portion sizes was not mandatory, but only asked for if no other recording (e.g., taking a food picture) was performed (138). To increase accuracy, some studies trained participants in portion size estimation (70,79,107), while others provided a scale and measurement cups and spoons (94) or asked participants to weigh the foods before consumption (110).…”
Section: Assessment Of Serving or Portion Sizesmentioning
confidence: 99%